Evaluasi Penerapan Anggaran Dana Desa Menurut Peraturan Pemerintah Nomor 60 Tahun 2014 - Tri Putri Puspa Wulandari; Husni Mubarak (Politeknik Negeri Bengkalis, 2020)
This article focus about Village funds are allocated in the APBN intended for villages that are transferred through the district/city regional revenue and expenditure budget and are used to finance government budgets, implementation of development, development, community development, and community empowerment. The government that requires government regulation number 60 of 2014 concerning village funds sourced from the state budget. Research 60 of 2014 in the village of Siak Kecil subdistrict Bengkalis regency. This study uses a qualitative method based on studies in the field data collection techniques used consist of observations interviews, documentation. Results of research the results of this study are as follows. For Lubuk Muda village budgeting. Sepotong and Tanjung Belit are in accordance with the DD implementation mechanism which in the village fud budgeting is a part of the non ministerial centeral budget expenditures as a village fund reserve post. For the allocation villages, Lubuk Muda, Sepotong and Tanjung Belit village are in accordance with the dd aaplication based on population data, area, poverty rate for DD distribution, Lubuk Muda, Sepotong and Tanjung Belit village are in accordance with the use of the village fund budget application. The village fund is channeled by the government to the city district, the distribution of the village fund is carried out by book entry from the RKUN to the RKUD.